2016
DOI: 10.1007/s00404-016-4227-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of total parenteral nutrition on postoperative recovery in patients treated for advanced stage ovarian cancer

Abstract: Postoperative TPN in ovarian cancer patients may be inadvisable because of the increased risk for complications. Moreover, in the hypoalbuminemic patients, TPN may have not only delayed their postoperative recovery and increased hospital stay duration, but further precipitated the manifestation of nosocomial sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…This could be due to the difference in the analyzed population between the two studies. However, in line with this study [ 34 ], we also found that serum albumin level was significantly lower in the TPN treated patients. Serum albumin often reflects elevation of systemic immune response and metabolism status as a result of traumatic injury and has been shown to be a significant predictor for operative morbidity and surgical outcome [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This could be due to the difference in the analyzed population between the two studies. However, in line with this study [ 34 ], we also found that serum albumin level was significantly lower in the TPN treated patients. Serum albumin often reflects elevation of systemic immune response and metabolism status as a result of traumatic injury and has been shown to be a significant predictor for operative morbidity and surgical outcome [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, another study has demonstrated significantly improved median survival for terminally ill ovarian cancer patients who received TPN [ 22 ]. In the present study, we found that TPN treatment can reduce the time of hospitalization as previously reported [ 3 , 14 , 15 ], but had no impact on time to restoration of bowel function and number of post-operative complications, which was suggested to be otherwise in a previous study [ 34 ]. This could be due to the difference in the analyzed population between the two studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with another previous study (31) and our recent findings (32), we found that serum albumin levels both before and after the nutritional intervention were significantly lower in the TPN treated patients. Serum albumin often reflects elevation of systemic immune response and metabolism status as a result of traumatic injury.…”
Section: Discussionsupporting
confidence: 93%
“…A number of laboratory parameters have been shown to be associated with impaired prognosis in patients with EOC including markers of inflammation, serum tumor markers, thrombocytosis, serum level of angiotensinconverting enzyme and cell-surface markers expressed by the ANTICANCER RESEARCH 38: 5127-5130 (2018) 5128 tumor cells (10)(11)(12)(13)(14). Interestingly, recently published studies investigated whether medical interventions such as antihypertensive medication or parenteral nutrition influence the prognosis of patients with cancer by altering circulating inflammatory markers or serum albumin levels (15,16). Our study is in line with the aforementioned data, as the independent prognostic factor ascertained in our study, namely the serum level of creatinine, can be changed by medical interventions.…”
Section: Discussionmentioning
confidence: 99%